ASTAXANTHIN MENGHAMBAT PERLEMAKAN HATI DAN PENINGKATAN KADAR SERUM GAMMA-GLUTAMYLTRANSFERASE PADA TIKUS WISTAR JANTAN YANG DIBERI MINYAK JELANTAH - Astrid Amanda Pangalela; I Wayan Weta; Iin Indrayani Maker (IJCNP : INDONESIAN JOURNAL OF CLINICAL NUTRITION PHYSICIAN, 2020)
ABSTRACT Non-alcoholic fatty liver can be triggered by used cooking oil consumption due to the formation of free radicals and the accumulation of fatty acids in the body. Astaxanthin is a powerful antioxidant that may be able to inhibit the pathogenesis of fatty liver. This study aims to determine the effect of astaxanthin in inhibiting fatty liver (steatosis) and levels of Gamma-Glutamyltransferase (GGT) in male Wistar rats given used cooking oil. An experimental study with Post-test Only Control Group Design was conducted on 36 male Wistar rats aged 3.5-4 months with an approximate bodyweight of 200-210 grams divided randomly into 2 groups. The control group was given 0.42 ml of used cooking oil + 0.5 ml of distilled water, and the treatment group was given 0.42 ml of used cooking oil + 0.2 mg of astaxanthin each day for 14 days. On day 15, blood tests and hepatic histopathology were performed to check GGT serum levels and steatosis. The comparative test was conducted to compare the results of the control and treatment groups. The results showed that the mean steatosis and GGT levels in the treatment group were significantly lower than the control group. It can be concluded that giving astaxanthin can inhibit fatty liver (steatosis) and increase GGT serum levels in male Wistar rats given used cooking oil. Keywords: Astaxanthin, Fatty liver, Gamma-glutamyltransferase, Used cooking oil